Errors in The Acquisition of Various Grammar Items by Vietnamese Students at Elementary Level: 初级水平越南学生习得各项语法项目的偏误情况 - Dang Thu Lan (Mandarinable: Journal of Chinese Studies, 2023)
This article uses test papers from students at Ho Chi Minh University of Banking (HUB) in Vietnam as the interlanguage corpus. According to the "Chinese Proficiency Grading Standards for International Chinese Language Education" (New Standads), we find out the grammatical items in which learners make errors and count their error rates, compared with Vietnamese expressions, analyze the cause of the error. The results show that in the band 1 grammar items of the “New Standard”, the proportion of Vietnamese students' errors in the total number of grammar items is relatively low: HSK1 class students have a total of 9 errors, accounting for 18.7% of the total grammar items in the band 1. In HSK2-3 class, Except for demonstrative pronouns, the error rate of these items decreased significantly, with 3 items having zero error rates. At the same time, 2 new error items appeared with the acquisition of new grammar points in this stage. The students in HSK1 class have a high error rate mainly due to the structural auxiliary word "的", the preposition "和" and "跟", the preposition "在" and the adverbial indicating the time. The high error rate among students in HSK2-3 class is mainly reflected in the special sentence structures of "了1、了2. The types of errors are mostly out of sequence or missing components. Therefore, when training Chinese to Vietnamese students, it is necessary to strengthen their expression order of "subject- time- object- location- action", which can solve multiple word order errors. In addition, for the teaching of "tenses", it is necessary to increase the repetition rate of learning materials and repeatedly practice using context, which can greatly improve students' bias situation.